KEAMANAN TRANSMISI DATA PADA SISTEM IOT MELALUI PENERAPAN METODE CHECKSUM SHA-256, AES-128 UNTUK PENCEGAHAN DATA TAMPERING - I Putu, I Putu Bayu Krisna Priastawan; Nugroho budhisantosa; Popong Setiawati; Imam Sutanto (Yayasan Literasi Sains Indonesia, 2025)
MQTT is a communication protocol in IoT that operates using a publish-subscriber scheme, where the publisher sends data to the broker and the data is forwarded to subscribers that are subscribed to the respective topic. Protecting data from cyberattack threats is one of the critical aspects, particularly against manipulation attempts such as data tampering attacks that can make it inaccurate and even potentially produce false information. Therefore, methods such as the SHA-256 checksum, the salt technique, and AES-128 can be utilized to prevent data tampering threats. Based on the testing results, the average detection and prevention rate of data tampering attacks reached 100%, and the average amount of data successfully received by the subscriber was 94% of the total topic data transmissions during the testing. The developed security system is not yet perfect, because the system can only prevent attacks on the subscriber side. To fully prevent data tampering attack, additional security measures such as TLS, SSL, or using port 8883 on MQTT are required so that communication can take place privately.